The Epidemiology of Community Clostridium difficile Infection: A Five-Year Population-Based Study on the Bailiwick of Jersey, Channel Islands. (27th February 2018) - Kumar, Shankar; Chis Ster, Irina; Pollok, Richard; Muscat, Ivan; Planche, Timothy D.
Abstract : We studied healthcare-associated and community-associated Clostridium difficile infection (CDI) in Jersey, Channel Islands (2008–2012). The Island's stable population has reliable denominator data, a clearly defined at-risk population, and healthcare contact that is easily followed. The vast majority of CDI cases had had recent healthcare contact, and true community-associated disease is extremely rare. Infect Control Hosp Epidemiol 2018;39:603–607